2019
DOI: 10.1186/s40246-019-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

What influences public views on forensic DNA testing in the criminal field? A scoping review of quantitative evidence

Abstract: Background Forensic DNA testing is a powerful tool used to identify, convict, and exonerate individuals charged of criminal offenses, but there are different views on its benefits and risks. Knowledge about public views on forensic DNA testing applied in the criminal field is socially valuable to practitioners and policymakers. This paper aims to synthesize quantitative evidence about the factors that influence public views on forensic DNA testing in the criminal field. Based on a systematic searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 65 publications
(161 reference statements)
0
34
0
2
Order By: Relevance
“…Continuing in the field of public perception, other authors have also expanded the literature on the social studies of forensic genetics, by conducting studies focused on public perceptions about DNA databases, whether through qualitative methodologies Machado & Prainsack, 2012;Wilson-Kovacs, Wyatt, & Hauskeller, 2012) or quantitative ones (an extensive review of the existing studies can be found at Machado & Silva, 2019). In this regard, we underscore the work of the sociologist Dana Wilson-Kovacs and colleagues (Wilson-Kovacs et al, 2012).…”
Section: Consolidation Of the Social Studies In Forensic Geneticsmentioning
confidence: 86%
See 1 more Smart Citation
“…Continuing in the field of public perception, other authors have also expanded the literature on the social studies of forensic genetics, by conducting studies focused on public perceptions about DNA databases, whether through qualitative methodologies Machado & Prainsack, 2012;Wilson-Kovacs, Wyatt, & Hauskeller, 2012) or quantitative ones (an extensive review of the existing studies can be found at Machado & Silva, 2019). In this regard, we underscore the work of the sociologist Dana Wilson-Kovacs and colleagues (Wilson-Kovacs et al, 2012).…”
Section: Consolidation Of the Social Studies In Forensic Geneticsmentioning
confidence: 86%
“…For example, the study by Machado and Prainsack (2012) notes how prisoners consider that having their genetic profile on a forensic DNA database managed by the police may reinforce the stigmatization towards individuals who have committed crimes (Machado & Prainsack, 2012). Other studies have also revealed that individuals from disadvantaged social groups and racial and ethnic minorities present a high degree of mistrust about the use of genetic evidence in the criminal justice system (Curtis, 2009;Duster, 2006;Machado & Silva, 2019).…”
Section: Consolidation Of the Social Studies In Forensic Geneticsmentioning
confidence: 99%
“…not known to provide information about specific hereditary characteristics" [6,7]. Almost all countries have some form of DNA legislation, but these laws are generally confined to traditional DNA forensics, that is, compiling DNA profiles or fingerprints from crime scene material and comparing these to profiles stored in forensic DNA databases, however, legal permissibility and practice of forensic of DNA phenotyping remains unregulated in most recent jurisdiction [4,8,9]. VISAGE, an EU-funded consortium project has been proposed to explore explores the social, ethical, and regulatory aspects of FDP, respectively [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…A large volume of published articles exist which contend, that the use of information of this kind raises a range of issues which are imperative to be discussed together in the light of other fundamental principles in addition to merely the public benefit stemming from the solution of crimes. These include public views, ethical principles such as personal autonomy, justice, dignity, confidentiality or solidarity, possible stigmatization and discrimination, legal principles such as due process and proportionality in addition to democratic values such as equality, security, transparency and pluralism [3][4][5]13].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of amplification technology linked to the analysis of STRs led to the availability of sufficiently sensitive and robust systems for the formation of efficient and effective DNA databases ( 39 ). A leading advancement in forensic DNA profiling was the establishment and expansion of centralised national criminal DNA databases ( 40 , 41 ). Since the comprehensive legislation was enacted in 1995 forensic scientists in the United Kingdom set up the first national DNA database that would hold both personal DNA profiles together with results obtained from crime scenes ( 42 ).…”
Section: Dna Databasesmentioning
confidence: 99%